Spontaneous corneal perforation in a patient with lamellar ichthyosis and dry eye - Turgut, Burak; Aydemir, Orhan; Kaya, Murat; Turkcuoglu, Peykan; Demir, Tamer; Celiker, Ulku (Dove Medical Press Ltd, 2009)
We report spontaneous corneal perforation in a patient with lamellar ichthyosis. The patient presented with complaints of pain, redness, diminished vision, and discharge in her right eye for 15 days. Visual acuities were light perception in the right and 20/400 in the left eye. Cicatricial ectropion in both lower eyelids and 2 mm perforation site in the center of the right cornea were observed. Lamellar ichthyosis was suspected because of scaling and excessive dryness of entire body skin and was confirmed by skin biopsy. Amniotic membrane transplantation and transient tarsorraphy was performed and systemic anti-ichthyosis therapy was started. The follow-up visits were not possible because of patient inconsistency. In patients with cicatricial ectropion secondary to ichthyosis, corneal health should be closely monitored because of the perforation risk.
Keywords: lamellar ichthyosis; cornea; spontaneous perforation